THE EFFECT OF INTRINSIC MOTIVATION AND COMMUNICATION ON EMPLOYEE CASHIER PERFORMANCE IN TRANSMART NGAGEL SURABAYA - Akhmad Rosidi; Bayu Airlangga Putra; Mochammad Arif (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to determine the relationship between intrinsic motivation and communication on improving the performance of cashier employees at Transmart Ngagel Surabaya. This research is quantitative research. With a population of 98 respondents. Data collection techniques using interviews, observation and questionnaires. Analysis of the data used is validity test, reliability test, classic assumption test and multiple linear analysis test. The results showed that the influence of intrinsic motivation and communication on the performance of the cashier employees at Transmart Ngagel Surabaya showed positive and significant results. The result of the F test is 69,428> F table 3.09 simultaneously. Partially intrinsic motivation of 6.464> t table 1.985 has a significant influence on employee performance, communication 4.066> t table 1.985 has a significant influence on employee performance.